Дюймовочка и другие сказки: сказки / редактор В. Гетцель - Гетцель В. (Читаем детям, 2011)
Экземпляры: ф.3 (20230512) / Инвентарный номер: 63499 / Цена: / Сис.шифр: 84(4)-4 / Авт.знак: Д 95 / ГРНТИ: 17.82.93 / ББК: 84(4)-42